The tomato mutation nxd1 reveals a gene necessary for neoxanthin biosynthesis and demonstrates that violaxanthin is a sufficient precursor for abscisic acid biosynthesis. (12th March 2014) - Neuman, Hadar; Galpaz, Navot; Cunningham, Francis X.; Zamir, Dani; Hirschberg, Joseph
Summary Carotenoid pigments are indispensable for plant life. They are synthesized within plastids where they provide essential functions in photosynthesis. Carotenoids serve as precursors for the synthesis of the strigolactone phytohormones, which are made from β‐carotene, and of abscisic acid (ABA), which is produced from certain xanthophylls. Despite the significant progress that has been made in our understanding of the carotenoid biosynthesis pathway, the synthesis of the xanthophyll neoxanthin has remained unknown. We report here on the isolation of a tomato (Solanum lycopersicum) mutant, neoxanthin‐deficient 1 (nxd1), which lacks neoxanthin, and on the cloning of a gene that is necessary for neoxanthin synthesis in both tomato and Arabidopsis. The locus nxd1 encodes a gene of unknown function that is conserved in all higher plants. The activity of NXD1 is essential but cannot solely support neoxanthin synthesis. Lack of neoxanthin does not significantly reduce the fitness of tomato plants in cultivated field conditions and does not impair the synthesis of ABA, suggesting that in tomato violaxanthin is a sufficient precursor for ABA production in vivo.